2020
DOI: 10.1371/journal.pone.0236533
|View full text |Cite
|
Sign up to set email alerts
|

Investigating hospital Mycobacterium chelonae infection using whole genome sequencing and hybrid assembly

Abstract: Mycobacterium chelonae is a rapidly growing nontuberculous mycobacterium that is a common cause of nosocomial infections. Here we describe investigation of a possible nosocomial transmission of M. chelonae at the Hospital of the University of Pennsylvania (HUP). M. chelonae strains with similar high-level antibiotic resistance patterns were isolated from two patients who developed post-operative infections at HUP in 2017, suggesting a possible point source infection. The isolates, along with other clinical iso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…We concluded that results are heavily dependent on the database of choice therefore, Hyb ASM might be a better approach for in depth analyses of WGS data. Although Hyb ASM has been used to study hospital Mycobacterium chelonae infections [59], extraintestinal pathogenic E. coli isolates [52] and one pan-drug-resistant K. pneumoniae isolate [60], the application of Hyb ASM for studying pathogenic factors in clinical samples is somewhat limited. In the current study, Hyb ASM showed reliable results for studying the clinical samples, specifically for the mixed culture as compared to Illum ASM and MinION ASM .…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that results are heavily dependent on the database of choice therefore, Hyb ASM might be a better approach for in depth analyses of WGS data. Although Hyb ASM has been used to study hospital Mycobacterium chelonae infections [59], extraintestinal pathogenic E. coli isolates [52] and one pan-drug-resistant K. pneumoniae isolate [60], the application of Hyb ASM for studying pathogenic factors in clinical samples is somewhat limited. In the current study, Hyb ASM showed reliable results for studying the clinical samples, specifically for the mixed culture as compared to Illum ASM and MinION ASM .…”
Section: Discussionmentioning
confidence: 99%
“…Genomes with a genetic similarity of ≥ 99.99% were considered related, and plausible outbreaks were investigated using traditional epidemiological methods. The threshold for genetic similarity was based on previous studies [ 32 , 33 ] and the latest nanopore accuracy data ( https://nanoporetech.com/accuracy ).…”
Section: Methodsmentioning
confidence: 99%
“…The human‐ and dog‐derived strains differed by only 1 SNV among the single copy core genes. Using the negative binomial distribution of SNVs from the assembly of Vibrio campbellii technical replicates as reference (Gu et al, 2020), the binomial test of 1 SNV between genomes results in a p ‐value >0.91, implying that these two isolates are identical. These microorganisms were genetically distinct (>50 SNPs difference) from C .…”
Section: Resultsmentioning
confidence: 99%
“…The human-and dogderived strains differed by only 1 SNV among the single copy core genes. Using the negative binomial distribution of SNVs from the assembly of Vibrio campbellii technical replicates as reference (Gu et al, 2020) 2).…”
Section: Uphs Cohort Osuwmc Cohortmentioning
confidence: 99%